2007
DOI: 10.1038/sj.ijo.0803614
|View full text |Cite
|
Sign up to set email alerts
|

High intake of palatable food predicts binge-eating independent of susceptibility to obesity: an animal model of lean vs obese binge-eating and obesity with and without binge-eating

Abstract: Objective: To determine the stability of individual differences in non-nutritive 'junk' palatable food (PF) intake in rats; assess the relationship of these differences to binge-eating characteristics and susceptibility to obesity; and evaluate the practicality of using these differences to model binge-eating and obesity. Design: Binge-eating prone (BEP) and resistant (BER) groups were identified. Differential responses to stress, hunger, macronutrient-varied PFs, a diet-induced obesity (DIO) regimen and daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
166
3
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(203 citation statements)
references
References 63 publications
21
166
3
7
Order By: Relevance
“…These associations are concordant with a body of research showing that for many individuals, foods high in fat and sugar tend to promote overeating and weight gain, both in humans and in animals, and that such foods are selectively preferred by obese individuals. 56 In addition, a recent study demonstrated that high intake of palatable food was a good predictor of binge eating in animals independent of their susceptibility to gain weight. 57 There is also evidence that satiety regulation of fat intake is less efficient than it is for other macronutrients, suggesting another mechanism whereby a fat preference contributes to overconsumption.…”
Section: Discussionmentioning
confidence: 99%
“…These associations are concordant with a body of research showing that for many individuals, foods high in fat and sugar tend to promote overeating and weight gain, both in humans and in animals, and that such foods are selectively preferred by obese individuals. 56 In addition, a recent study demonstrated that high intake of palatable food was a good predictor of binge eating in animals independent of their susceptibility to gain weight. 57 There is also evidence that satiety regulation of fat intake is less efficient than it is for other macronutrients, suggesting another mechanism whereby a fat preference contributes to overconsumption.…”
Section: Discussionmentioning
confidence: 99%
“…Eating frequency and type of nutrients in the meal are associated with metabolic changes 23,24 and glycemic homeostasis 25 . Therefore, the same food was offered on the experimental day to the participants, and also the same quantity of food, in order to avoid acute release of any appetite-related hormone.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this training schedule and these diet conditions because previous home-cage food consumption studies have shown that rats placed on a restricted diet and given intermittent access to palatable food develop binge-like eating behaviour (Colantuoni et al, 2002;Corwin and Buda-Levin, 2004;Boggiano et al, 2007;Figlewicz et al, 2007;Avena et al, 2008), and become hypersensitive to the effect of stress on palatable food intake (Hagan et al, 2002(Hagan et al, , 2003. We also chose our diet conditions based on two other considerations.…”
Section: Methodsmentioning
confidence: 99%